Analysis of a planar differential system arising from hematology - PARAJDI, Lorand Gabriel; PRECUP, Radu (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
A complete analysis of a planar dynamic system arising from hematology is provided to confirm the conclusions of computer simulations. Existence and uniqueness for the Cauchy problem, boundedness of solutions and their asymptotic behavior to infinity are established. Particularly, the global asymptotic stability of a steady state is proved in each of the following cases related to leukemia: normal, chronic and accelerated-acute. Mathematics Subject Classification (2010): 34A34, 34D23, 93D20.